INFLUENCE OF METABOLIC SYNDROME ON DENTAL IMPLANTS HEALTH - Mihaela Doru-Butnaru; Dora-Maria Popescu; Dorin-Nicolae Gheorghe; Maria-Alexandra Martu; Luminita Lazar; Petra Surlin (Romanian Journal of Medical and Dental Education, 2020)
The metabolic syndrome is a complex pathology, multisystemic, with numerous consequences that include: high blood sugar, hypertension, visceral obesity, dyslipidemia with high levels of triglycerides (TG) and low levels of HDL.